ANALYSIS OF THE EFFECTIVENESS OF GOVERNMENT ASSET MANAGEMENT USING THE SAKTI AND SIMAN APPLICATIONS AT THE BPS (Central Bureau of Statistics) OF SOUTH SULAWESI PROVINCE - Patanda, Alberthin; Verawaty, Verawaty; Anshar, Muh. Ashary (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the effectiveness of State Asset Management (BMN) at the Central Bureau of Statistics (BPS) of South Sulawesi Province through the utilization of two key digital systems: the Institutional Level Financial Application System (SAKTI) and the State Asset Management Information System (SIMAN). Both systems serve as integrated tools that support accurate, efficient, and accountable recording, administration, monitoring, and reporting of government-owned assets. The research employed a qualitative descriptive method with a case study approach. Data were obtained through in-depth interviews with asset management personnel at BPS South Sulawesi and with supervisory institutions, namely DJKN and KPKNL. Data analysis was carried out through categorization, data reduction, and visualization using the R libraries wordclouds and ggplot. The findings reveal that implementing SAKTI and SIMAN has significantly improved transparency, data accuracy, and process efficiency in BMN management. However, several challenges persist, including limitations in human resource competencies, data inconsistencies across systems, delays in updating asset information, and technical constraints on system access and connectivity. Strengthening system integration, enhancing staff capacity, improving inter-unit coordination, and upgrading technological infrastructure are essential further to improve the effectiveness and accountability of state asset management.